2D and 3D imaging of a buried prehistoric canoe using GPR attributes: a case study. Issue 4 (1st March 2013) - Zhao, Wenke; Tian, Gang; Wang, Bangbing; Forte, Emanuele; Pipan, Michele; Lin, Jinxin; Shi, Zhanjie; Li, Xuejing
ABSTRACT: We apply Ground Penetrating Radar (GPR) to detect a prehistoric canoe at the Maoshan site, Zhejiang Province, China. A complex attribute analysis of the GPR data allows enhancing the precision in target detection and provides more details about the canoe and the burial environment. The burial depth of the bottom interface of the prehistoric canoe is detected and the integrity of the whole canoe is assessed through a GPR survey. Difficulties in the application of dense sampling of 2D and pseudo 3D GPR data originate from micro‐topographical disturbance that specifically affects the pseudo 3D investigation results obtained from high‐frequency antennas. Data processing and advanced imaging techniques can only remove part of such effects. The research demonstrates that GPR can successfully image wooden cultural relics buried in the shallow subsurface with ultra, high‐density trace spacing and high‐frequency antennas even in totally saturated clay‐rich soils based on 2D profiles and pseudo 3D methodologies, characterized by tight (cm) cross‐line/in‐line spacing.